Change in Ubiquitin Proteasome System of Grass Carp Ctenopharyngodon idellus Reared in the Different Stocking Densities - Sun, Yiqing; Liang, Xiao; Chen, Jie; Tang, Rong; Li, Li; Li, Dapeng (Frontiers in Physiology, 2018)
The ubiquitin proteasome system (UPS) is a highly regulated mechanism of intracellular protein degradation and turnover. To evaluate the effect of crowding stress on the UPS in fish, grass carp (Ctenopharyngodon idellus) were randomly reared at low stocking density (LSD, 0.9 kg m-2) or high stocking density (HSD, 5.9 kg m-2) for 70 days. The expression of the genes regulating UPS, stress-related parameters, and profiles of amino acid in white muscle as well as growth rate of fish reared at two stocking densities were investigated. Fish exhibited significantly higher growth rate in the LSD group compared to the HSD group. Serum concentrations of cortisol, total protein, and glucose did not vary significantly in fish between two groups. There was no significant difference in the mRNA levels of nrf2, keap1, and hsp90 in white muscle of fish stocked at two densities at the endpoint of the experiment. In the UPS pathway, the expressions of ub, chip, psmc1 in the LSD group were significantly higher than those in the HSD group (P < 0.05). Ubiquitinated protein level and the content of 3-Methylhistidine elevated significantly in the LSD group (P < 0.05). The mRNA levels of mafbx, murf1, and s6k1 in the LSD group were significantly higher than those in HSD group (P < 0.05). These results illustrate that the fish cultured in lower stocking density would exhibit a greater growth rate and a fast protein turnover in muscle.